Downregulation of L-arginine metabolism in dendritic cells induces tolerance to exogenous antigen - Simioni, Patricia U. [UNESP]; Fernandes, Luis G.R.; Tamashiro, Wirla M.S.C. (SAGE Publications, 2017)
Dendritic cells (DC) are potential tools for therapeutic applications and several strategies to generate tolerogenic DCs are under investigation. When activated by cytokines and microbial products, DCs express mediators that modulate immune responses. In this regard, the metabolites generated by the activities of inducible nitric oxide synthase (iNOS) and arginase in DCs seem to play important roles. Here, we evaluated the effects of adoptive transfer of DCs generated in vitro from bone marrow precursors (BMDC) modulated with L-NAME (Nω-nitro-L-arginine methyl ester) and NOHA (NG-Hydroxy-L-arginine), inhibitors of iNOS and arginase, respectively, upon the immune response of the wild type (BALB/c) and OVA-TCR transgenic (DO11.10) mice. The modulation with L-NAME increased CD86 expression in BMDC, whereas treatment with NOHA increased both CD80 and CD86 expression. Adoptive transfer of either L-NAME- or NOHA-modulated BMDCs to BALB/c mice reduced the plasma levels of ovalbumin-specific antibody as well as proliferation and cytokine secretion in cultures of spleen cells in comparison adoptive transfer of non-modulated DCs. Conversely, transfer of both modulated and non-modulated BMDCs had no effect on immune response of DO11.10 mice. Together, these results show that the treatment with iNOS and Arg inhibitors leads to increased expression of co-stimulatory molecules in DCs, and provides evidences that L-arginine metabolism may be an important therapeutic target for modulating immune responses in inflammatory disorders.
Keywords: arginase; co-stimulatory molecules; cytokine; dendritic cell (DC); nitric oxide; proliferation